E-Government and Democracy: A Boost to Sustainable Development - Chukwudi, Celestina Ekene; Bello, Wasiu; Adesemowo, Modupeola Morenike (Universitas Medan Area, 2023)
Sustainable development of any progressive society is expected to have in it a level of citizens’ participation which is an outcome of a democratic system. In our society today, e-government as a practice has contributed to the style of democracy and political development. Some societies have failed to apply the indices of e-government and democracy which has led to their inability to witness development that is beneficial to them and their coming generation. This paper is to explore numerous ways that e-government and democracy have contributed towards sustainable development in society. The paper also is set to inquire into various challenges such as finance, insecurity, and lack of skills facing e-government and democracy and strategies that can lead to the strengthening of e-government and democracy. The study adopts a qualitative method where secondary data are gathered and utilized. These data are gathered from Newspapers, Magazines, books, journals, and conference materials. Internet sources are also obtained from reliable platforms that serve academic purposes. Governance theory is adopted for the analysis of this work to drive home the impact of e-government and democracy. The paper concludes that e-government and democracy despite challenges faced have impacted in no small measures towards sustainable development that stands to benefit people today and in the future. It is then recommended that continuous and standard innovation and transformation must be embraced for a robust developmental process in the arena of e-government and democracy.